Optimization of sterlet sperm concentration for cryopreservation - Nascimento, João Pedro (2021)
One of the critical points in low temperature storage is the expense of storage capacities. Moreover, sperm concentration in a sample is not only a parameter for effective use of a cryobanks but also a parameter affecting cryopreservation outcomes. Sturgeon sperm in comparison to other species is significantly less concentrated due to the specificity of sperm maturation process, during which sperm is mixed with urine. In this study, we evaluated whether the artificial modification of the sterlet spermatozoa concentration before freezing can be useful during the routine application of sturgeon sperm cryopreservation. The sperm was first concentrated by centrifugation of native sperm samples. Then, the excess of seminal fluid was collected. The concentrated sperm samples were further diluted with the same seminal fluid to obtain different sperm concentrations in suspension, and they were subjected to freeze-thawing. The percentage of postthaw sperm motility depended on the sperm concentration in the samples. The highest post-thaw sperm motility was found in sperm samples with concentration of 0.2 and 1 × 109 spz mL 1. The sperm concentration of 3 × 109 spz mL 1, which is higher than the native sperm concentration in sterlet, was found to be appropriate for use in cryopreservation procedures since the sperm fertilizing ability remained at a high level even though a significant decline in percentage of sperm motility was observed. These findings supported the conclusion that the procedure of artificially increasing the sperm concentration before freezing could be useful for the reduction of the volume kept in cryostorage and to decrease the sample volume required for artificial fertilization.